Karakteristik Campuran AC-WC dengan Penambahan Limbah Plastik Low Density Polyethylene (LDPE) - Razak, Bustamin Abd.; Erdiansa, Andi (INTEK: Jurnal Penelitian, 2016)
This study aims to determine the effect of using plastic waste Low Density polyethylene ( LDPE ) on the characteristics of a mixture of AC- WC . This study used five plastic content variation is 1 % , 2 % , 3 % , 4 % , and 5 % to determine the characteristics of the AC- WC . The method used in this study is a test that aims marshall know the characteristics , the performance of the mixture , and the optimum level of use of asphalt in the mix AC- WC . The results showed that the characteristic value AC- WC that include the percentage of plastic content obtained from the testing of 1 % -5 % of the optimum bitumen content , if the levels of plastic in bitumen is added, the value of stability , flow , and marshall quotient increase and decrease unstable , while the value of VFB and the density increases, and the value of VIM and VMA decreases.